The Effectiveness of the Master of Flood Preparedness (MOFP) in Elevating Malaysian Youths' Awareness of Flood Preparedness - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Soon-Yew, Ju; Noor Amira Syazwani, Abd Rahman; Amirudin, Mohd Zani; Lai-Kuan, Kong (Human Resource Management Academic Research Society (HRMARS), 2023)
The frequency of floods in Malaysia is on the rise, leading to the loss of numerous lives and property. The youth population is particularly vulnerable and susceptible to the dangers posed by floods if they lack preparedness. Hence, they must enhance their level of preparedness to effectively mitigate the adverse consequences of floods. To address this need, the Master of Flood Preparedness (MOFP) was created to increase awareness of flood preparedness among young individuals. This game-based learning approach encompasses three key components: flood preparedness-related e-books, a game board, and play cards. These elements are integrated into a game format to deliver and enhance youth awareness of flood preparedness. Therefore, the primary objective of this study is to assess the impact of the MOFP on increasing flood preparedness awareness among Malaysian youth. The study employs purposive sampling, with 120 individuals aged between 15 to 40 years old serving as participants. Through a descriptive approach, the study reveals that a majority of the youth respondents hold a positive perception of the MOFP's usability. Furthermore, a notable percentage of the participants acknowledged the user-friendliness of the MOFP. Moreover, their levels of awareness experienced a substantial increase following their exposure to the MOFP, underscoring its effectiveness in augmenting youth awareness regarding flood preparedness. It is anticipated that this game-based learning approach will prove beneficial to various institutions, including schools, universities, policymakers, and individual youth, as it offers a means to deliver and enhance flood preparedness awareness among the youth population.